Electric resistivity of aluminum due to the structure state evolution under active loading near the yield limit - Nikiforenko, V.N.; Bosin, M.E.; Krasnikova, Z.A.; Solodilov, S.A. (Functional Materials, 2004)
The structure state evolution near the yield limit of polycrystalline aluminum of various purity grades under active loading has been studied by electric resistance method. Characteristic parameters of the structure state have been determined, namely, the effec -tive dipole height and coefficients of dislocation interaction. It has been shown that, no matter what is the material purity grade, the onset of the plastic flow, the deforming stress, and the electric resistance change are defined by the dipole structure formation. Вблизи предела текучести методом электросопротивления изучена эволюция структурного состояния при активном нагружении поликристаллического алюминия разной степени чистоты. Определены характерные параметры структурного состояния: эффективная высота диполей, коэффициенты взаимодействия дислокаций. Показано, что независимо от степени чистоты деформируемого металла, начало пластического течения, деформирующее напряжение и изменение электросопротивления определяются формированием дипольной структуры. Поблизу границі текучості методом електроопіру досліджєно єволюцію структурного стану шляхом активного навантажування полікристалічного алюмінію різного ступеня чистоти. Визначено характерні параметри структурного стану: ефективна висота диполів, коефіцієнти взаємодії дислокацій. Показано, що, незалежно від ступеню чистоти металу, що деформується, початок пластичної плинності, деформуюча напруга та зміна електроопіру визначаються формуванням дипольної структури.